Faktor-faktor yang Memengaruhi Keputusan Penggunaan E-Wallet - Irfan Ardiansyah; Sendya Keren; Desti Dirnaeni; Christera Kuswahyu Indira (INVESTASI : Inovasi Jurnal Ekonomi dan Akuntansi, 2025)
Technological advancements have driven significant changes in payment systems, including the increasing use of e-wallets as fast, convenient, and secure transaction tools. This study aims to analyze the effects of perceived usefulness, perceived ease of use, promotion, perceived risk, and trust on decisions to use e-wallets. The study uses a sample of 125 respondents, selected through non-probability sampling with a purposive sampling method. The analytical method employed is quantitative primary data analysis, with the following testing stages: validity test, reliability test, normality test, heteroskedasticity test, multicollinearity test, F-test, t-test, and coefficient of determination (R²). The data used are primary data obtained through the distribution of questionnaires and processed using SPSS software. The results indicate that perceived usefulness, perceived ease of use, promotion, perceived risk, and trust simultaneously have an effect on usage decisions. Partially, perceived usefulness and promotion have a significant effect on usage decisions, while perceived ease of use, perceived risk, and trust do not have a partial effect on usage decisions. The most dominant variable influencing e-wallet usage decisions is promotion..